Implementasi Nilai-Nilai Moderasi Beragama Masyarakat Perbatasan Ri-Malaysia Di Desa Sungai Limau Kecamatan Sebatik Tengah Kabupaten Nunukan - Wahyuddin Wahyuddin; Ismail Ismail; Habibah Habibah (Journal on Education, 2024)
This research aims to gain a deeper understanding of the factual situation of the community, obtain insights into the community's views on religious moderation, and explore how religious moderation is implemented in Sungai Limau Village, Sebatik Tengah District, Nunukan Regency. The type of research used is qualitative research with a phenomenological approach. Data collection techniques include in-depth interviews, participant observation, and documentation, with data sources determined through purposive sampling and snowball sampling. Data analysis uses the phenomenological model developed by Creswell. The results show that the implementation of religious moderation values in Sungai Limau Village, at the RI-Malaysia border, includes practices such as national commitment, tolerance, anti-violence, and accommodation of local culture. The implementation strategy involves the active role of the village government, the formation of the youth community "Om Joko," and support from various institutions and stakeholders, including the Ministry of Religious Affairs and local educational institutions. The impacts include conflict reduction, increased friendship and acceptance of differences, strengthened faith, progress in various aspects of life, and a harmonious life.